Climatology of Hail in Central Europe - Suwała, Katarzyna; Bednorz, Ewa (Quaestiones Geographicae, 2013)
Taking into consideration the spatial variability of the occurrence of hail in central Europe in the warm season (April - September) during the years 1966-2010, five hail regions were distinguished by Ward’s group hierarchy method. For this purpose the daily data of hail occurrence were used. Circulation patterns responsible for hail precipitation at each cluster of stations were analysed using Reanalysis data (NCEP/NCAR). Composite maps of the sea-level pressure, 500 hPa geopotential height and 850 hPa-level temperature means were constructed for the days with hail. Additionally, anomalies of the values of each parameter were presented. It was found that more than 65% of hail events were recorded from April to June, with May as the hail-peak month. In all five distinguished regions hail precipitation was associated with negative anomalies of SLP and 500 hPa heights over Europe, most often with low-pressure systems developing within colder than usual air mass.